(-11)-8+1-(-6)=x

Simple and best practice solution for (-11)-8+1-(-6)=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-11)-8+1-(-6)=x equation:


Simplifying
(-11) + -8 + 1 + -1(-6) = x
-11 + -8 + 1 + -1(-6) = x

Multiply -1 * -6
-11 + -8 + 1 + 6 = x

Combine like terms: -11 + -8 = -19
-19 + 1 + 6 = x

Combine like terms: -19 + 1 = -18
-18 + 6 = x

Combine like terms: -18 + 6 = -12
-12 = x

Solving
-12 = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-12 + -1x = x + -1x

Combine like terms: x + -1x = 0
-12 + -1x = 0

Add '12' to each side of the equation.
-12 + 12 + -1x = 0 + 12

Combine like terms: -12 + 12 = 0
0 + -1x = 0 + 12
-1x = 0 + 12

Combine like terms: 0 + 12 = 12
-1x = 12

Divide each side by '-1'.
x = -12

Simplifying
x = -12

See similar equations:

| 4x+2=x-11 | | (-3)+5+(-5)+12=x | | x/2+3=1/2 | | 6+(-7)+(-5)-(-2)=x | | 6y=45-3y | | 7+(-1)+12-7=x | | (-11)-(-14)+7=x | | 9+6(2)7n= | | 0.5x-1.4=1.1 | | (-7)-(-2)-9=x | | -6-1=-32y+32 | | 16-(-13)-(-5)=x | | 6(y-4)=5[17-3(2y-13)] | | 4-5+7k=33 | | -9-200x+(0.015)(100)= | | (-16)-6+(-5)=x | | 12+0.4(x-2)=10 | | 6(x+2)+4=-6 | | 52x=104 | | 8y-5=6y+7 | | -33m-14=85 | | 5x+5x+3+8=5x+4+4x | | -r+259=-124 | | -2x^2+12x+3=0 | | 3(3+2r)=5-6(r+2) | | 3(2x-4)=5(x+6) | | 7x-6-4x=4x-3 | | 2.1x+1=7 | | 9x-3x=-26+2 | | 7-7x=29x+21 | | 17X^43=100000 | | 145-13= |

Equations solver categories